Jidangga-7 ameliorates non-small cell lung cancer by regulating gut microbiota function - Yue, Changcheng; San, Chula; Deng, Shichao; Wang, Jingjing; Shen, Xueying; Wang, Hongqing; Huang, Liyan; Bu, Renbatu; Wang, Dong (Frontiers in Microbiology, 2025)
ObjectiveThis study aims to assess the effects of Jidangga-7 on enhancing gut microbiota function in non-small cell lung cancer.Materials and methodsEighteen mice were screened and randomly divided into three groups: a control group, a model group with induced non-small cell lung cancer, and a treatment group receiving Jidangga-7. A549 tumor cells were implanted in the mice, and tumor formation was monitored. Upon successful tumor induction, the treatment group received Jidangga-7 via oral gavage, while the other groups received an equivalent volume of saline. After the final dose, intestinal tissues were collected from each group, and microbial amplicon 16S analysis and non-extensive targeted metabolomics were employed to characterize intestinal fiber and associated metabolites.ResultsBy quantifying the contribution of individual species to the variations between the groups, the Sipmer results highlighted the top 10 species and their abundance that contribute to the differences between the two groups. Specifically, Jidangga-7 demonstrated a regulatory effect on various taxa such as Gammaproteobacteria, Bacilli, and Desulfovovoviridae. At the family level, administration of Jidangga-7 exhibited a regulatory effect on families including Desulfovibrionaceae, Lachnospiraceae, and Eggerthellaceae, compared to the model group. In untargeted metabolomics analyses, principal component analysis effectively differentiated the groups from one another. Subsequently, metabolites with a variable importance in projection score > 1 were screened. The Kyoto Encyclopedia of Genes and Genomes pathway analysis revealed 20 metabolite pathways, encompassing metabolism of cofactors and vitamins, bacterial metabolism, antimicrobial pathways, and xenobiotics biodegradation and metabolism.ConclusionJidangga-7 exerted a positive influence on the intestinal microbial environment in mice with non-small cell carcinoma, ameliorating the dysbiosis induced by non- small cell lung cancer. This intervention inhibited the growth of pathogenic bacteria while fostering the growth of beneficial strains.